The legacy of Circle women's engagement with the Bible: Reflections from an African male biblical scholar - Togarasei, Lovemore (Verbum et ecclesia, 2016)
The entry of women into religious and theological studies has revolutionised the modus operandi of these disciplines. Especially with the formation of the Circle of Concerned Women Theologians, the study of these disciplines has never been the same. In this article, an attempt is made to consider the legacy of women theologians in the area of biblical interpretation. Specifically, the article looks at how members of the Circle have interpreted the Bible in their quest for a theology that responds to African women's experiences. The article discusses Circle biblical scholars' methods of interpreting the Bible, what they have managed to achieve, as well as pointing out areas that still call for attention. It concludes that Circle biblical scholars, like all African Biblical Interpretation, are engaged scholars who serve both the need for intellectual growth as well as solving the pressing needs of their societies.Intradisciplinary and/or interdisciplinary implications: This article primarily focuses on how members of the Circle of Concerned Women Theologians have interpreted the Bible in their quest for justice. It therefore engages several disciplines: biblical interpretation, theology, gender, politics, health, and so on.Keywords: African Biblical interpretation; Women theologians; Bible; legacy;engaged Biblical Scholarship